Analisis Awal Gerak Butiran pada Transport Sedimen Tanah Gambut Jenis Fibrik - Pratama, Fernando; Sigit Sutikno; Rinaldi (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2023)
Peat beaches are beaches whose land can be easily abraded than beaches with other types of land. This is due to the light density of peat soil so that it can be easily carried away by the flow of sea water. One of the peat beaches in Indonesia whose coastline has changed significantly in recent decades is the peat beach on Bengkalis Island, Riau Province. Peat samples were taken from Tanjung Jati Beach, Perapat Tunggal Village, Bantan District, Bengkalis Island, Bengkalis Regency, Riau Province and then the sample is carried out an initial motion analysis on peat soil sediment transport. The peat sample that is obtained is a type of fibric peat soil. This research is a basic research that aims to determine at what speed the peat soil begins to move by the flow of water so that it can be seen the relationship between flow velocity and particle diameter at the beginning of the particle movement. The analysis was carried out by visual observation during simulation in the laboratory using a modified flume which was then compared with the results of Shields' theoretical calculations. Simulations were also carried out using sand sediment as a comparison. The flume flow velocity is determined from 0.00989 m/s to 0.10112 m/s for peat material, and 0.03973 m/s to 0.18900 m/s for sand material. The velocity is considered to have met the required simulation conditions, starting from the sediment not moving, starting to move, and being carried away by the flow. The results of the analysis carried out show that the peat material begins to move at a lower speed than the sand material. This is due to the specific gravity of the peat material being lighter than the specific gravity of the sand material as a comparison. This research is also expected to be a reference for further research on related topics. Keywords : Peat, Flow Velocity, Initial Particle Motion, Critical Shear Stress, Shields Theory